Debate - From Palermo to the Streets of Oslo: Pros and cons of the trafficking framework - Økland Jahnsen, Synnøve; Skilbrei, May-Len (Anti-Trafficking Review, 2015)
The development of Norwegian anti-trafficking efforts and how they relate to obligations set forth by the United Nations Trafficking Protocol (also known as the ‘Palermo Protocol’) illustrates some of the constraints connected to international policymaking. While national trafficking policies on paper are in alignment with the definitions and priorities in the Protocol, the local and institutional context simultaneously influence how these international ambitions are interpreted and implemented. Thus, we argue that to understand the impact of the Protocol one must necessarily explore how it interacts with national agendas and instruments